English Syllabus for Accounting Students and the Needs of English in Business World - Suprato, Djuria; Dewi, Ienneke Indra; Paulina, Christine (Lingua Cultura, 2018)
This research aimed to evaluate English courses and syllabus in Bina Nusantara University, particularly in the accounting department, whether it was appropriate in the workplace. This study was conducted by interviewing 54 Bina Nusantara university graduates from Accounting department of 2013-2014 and three from big four public accountant firms in Jakarta. The result of the interview was analyzed qualitatively. The purpose of the interview was to get more detailed information about the benefit of English courses that they had at Bina Nusantara University. Besides that, the researchers had also interviewed with some public accounting firms in Jakarta to find out the level of English skills required and the standard scoring system used as a reference in their companies. With structured data collection, it can be concluded that the students need to practice English to improve the communication skills of speaking and writing to get good reports in English. Bina Nusantara University has provided adequate training, and the results can be felt by the graduates who are now working in multinational and international companies.